2008
DOI: 10.1080/08039480801984263
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ethnicity and self-reported health on psychological well-being: A comparative study of Kurdish-born and Swedish-born people

Abstract: Immigrants with self-reported Kurdish ethnicity (men, n=111; women, n=86) in Sweden from the national sample of immigrants aged 27-60 and 1407 Swedes (1996) were studied. Unconditional logistic regression was performed using the Stata Software program. In the logistic model adjusted for age, sex, employment and self-reported health, the odds ratio for Kurdish-born subjects for having poor psychological well-being is twice as high as for Swedish-born subjects. Subjects with poor self-reported health had more th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
(34 reference statements)
4
16
0
Order By: Relevance
“…The finding that the subjective general health evaluation was related to the well-being scores instead of the mere presence or absence of disease strengthens the validity of the scale, confirming that it serves the purposes for which it was designed. Moreover, this is consistent with previous studies, which found an association between subjective self-reported health and psychological well-being [19] but not objective health-related variables [20].…”
Section: Discussionsupporting
confidence: 93%
“…The finding that the subjective general health evaluation was related to the well-being scores instead of the mere presence or absence of disease strengthens the validity of the scale, confirming that it serves the purposes for which it was designed. Moreover, this is consistent with previous studies, which found an association between subjective self-reported health and psychological well-being [19] but not objective health-related variables [20].…”
Section: Discussionsupporting
confidence: 93%
“…Eastern European, Latin American and Other Non-Western workers also had an increased risk of mental distress. This finding is in accordance with prior research which has also shown mental health disparities among some migrant background groups in Sweden, including persons from former Soviet countries [47], Latin American countries [48] and Other Non-Western countries [49,50] when compared to native born Swedish persons. As good mental health is widely recognized as a core component of overall health and well-being [51] and is vital in the successful management of working life stressors and demands [52], reducing mental health inequalities among the foreign born population could not only improve health outcomes but also labor market participation.…”
Section: Discussionsupporting
confidence: 93%
“…Good mental health is more likely an indicator of a good sense of autonomous well-being. The result is supported by the findings of Taloyan, Sundquist, and Al-Windi (2008) [13] that somatic pains and gastrointestinal complaints are significantly and independently related to poor psychological well-being. On the contrary, the study of Roothman, Kirsten, and Wissing (2003) [14], reported that somatic symptoms are not significantly correlated to psychological well-being.…”
Section: Specific Component Of Mental Health and Psychological Well-bsupporting
confidence: 66%